Marketing Countries, Places, and Place-associated Brands - Papadopoulos, Nicolas; Cleveland, Mark (Edward Elgar Publishing, 2021)
2020 has clearly been the year in which most people on this planet, most organisations, most economic sectors, most government agencies, had to reassess their priorities. Who and what contributes most to life; the economy; society? This opinion piece ponders the question of how place branding will be judged and where it might go in the coming years.